2017
DOI: 10.1536/ihj.16-328
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparative Study on the Efficacy of Intracoronary Infusion of Autologous Bone Marrow Mononuclear Cells and Mesenchymal Stem Cells in Patients With Dilated Cardiomyopathy

Abstract: SummaryStem cell therapy has shown therapeutic benefit in dilated cardiomyopathy (DCM), but doubt remains about the most appropriate stem cell subpopulation. The current study compared the efficacy of intracoronary administration of bone marrow mononuclear cells (BMMC) or mesenchymal stem cells (BMSC) in patients with DCM.Fifty-three patients with DCM and reduced (< 40%) left ventricular ejection fraction (LVEF), were randomized to intracoronary infusion of BMMC (BMMC group, n = 16) or BMSC (BMSC group, n = 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 34 publications
(74 reference statements)
0
54
0
Order By: Relevance
“…As shown in Table 1, all nine studies were randomised controlled trials, four [5, 1113] of which were double-blind trials; two [17, 19] were single-blind trials, and three [14–16] did not show the blind method. A total of 612 patients with HF were included, of which 263 and 304 underwent MSC and placebo treatment, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, all nine studies were randomised controlled trials, four [5, 1113] of which were double-blind trials; two [17, 19] were single-blind trials, and three [14–16] did not show the blind method. A total of 612 patients with HF were included, of which 263 and 304 underwent MSC and placebo treatment, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-five patients from one study [19], who underwent mesenchymal precursor cells (MPC) treatment, were also enrolled, because MPC shares many of the same phenotypic features as MSCs [20]. Among these studies, the origins of MSCs are varied: from autologous bone marrow in six studies [5, 11, 12, 14, 16, 17], from allogenic bone marrow in one study [19] and from allogenic umbilical cords in two studies [13, 15]. MSCs were delivered by intracoronary injection in three studies [14–16], by transendocardial stem cell injection (TESI) in four studies [5, 11, 12, 19] and by peripheral intravenous injection in two studies [13, 17].…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of thrombotic or thrombo-embolic events were reported in a total of 24 RCTs (n = 1112 patients) [20,21,26,29,32,33,37,40,50,56,58,60,63,66,69,70]. In the pooled analysis there was no significant increase in the risk of thrombotic/thrombo-embolic events for MSCs as compared to the control group (RR = 1¢14, 95% CI = 0¢67À1¢95, I 2 = 0%; see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple clinical trials have suggested that cell-based treatments offer viable therapeutic approaches across a variety of pathological conditions [60, 61]. A majority of the trials evaluated the effects of locally or systemically delivered bone marrow MSC [4, 62, 63] as well as endothelial progenitor cells [64, 65] and ASC [60]. At the same time, growing recognition of the negative influence of aging [6668], diabetes [69], and various environmental exposures [38, 70] on the biology of stem/progenitor cells prompts evaluation of the impact of these factors on the therapeutic potential of regenerative cells.…”
Section: Discussionmentioning
confidence: 99%